AN ANALYSIS OF STUDENT BOREDOM LEARNING DURING THE COVID 19 PANDEMIC IN ELEMENTARY SCHOOL JAKARTA, INDONESIA - Nafiah, Maratun; Lestari, Ika; Zahra, Afnitya (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2021)
Almost all sectors of life have felt the impact of the COVID-19 pandemic. Education is one of the sectors that feel the effect. Schools conduct distance learning to minimize the spread of the COVID-19 virus. As a result, many students experience various emotions, one of which is boredom. This study analyzes learning boredom between male and female elementary school students in Jakarta, Indonesia, during the COVID-19 pandemic. The research method used is descriptive quantitative with data in the form of a closed questionnaire where respondents are given five alternative answers. Furthermore, it is investigated whether there is a difference in boredom between men and women. This research was conducted with 23 male students and 20 female students in elementary school. The results showed boredom in male and female students caused by psychological factors, situational factors, and cultural factors. There are differences in learning boredom between male and female students, but not statistically significant.